Budowanie reputacji przedsiębiorstwa poprzez inicjatywy społeczne - dylematy i wyzwania - Głuszek, Ewa (Corporate social initiatives undertaken to support corporate reputation - dilemmas and challenges, 2007)
Corporate Social Initiatives are major activities undertaken by a Corporation to build its reputation on the market. There are many reasons that firms should implement practices demonstrating social responsibility, but there are many others indicating that they should not. Ali these pros and cons dilemmas are discussed in the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 160-171